HF ANTENNA GAIN PATTERN MEASUREMENTS: EXPANDED LITTLE IDA PROGRAM - Simons, Joseph J; Wilson, Frederick C; Schneible, Richard A (1968)
The report describes the data collection, reduction, and processing techniques employed in an antenna gain measurements program. This gain measurements program is an integral part of the overall Expanded Little Ida effort. The gain patterns of transmitting antennas located at Thule, Greenland; Keflavik, Iceland; and Coco Solo, Panama Canal Zone were determined and the results reported herein. Descriptions of the instrumentation (site and aircraft) used to obtain the data, and descriptions of the manual and computer processing methods employed are discussed.